Pengembangan Media Kantong Mufrodat dalam Pembelajaran Bahasa Arab untuk Siswa Kelas IX SMP IT Ummi Ayuni Perbaungan - Deni Hazmi; Harun Al- Rasyid (MANAZHIM, 2023)
The low vocabulary mastery of students in learning Arabic requires solutions and alternatives, one of which is using pocket mufrodat learning media. This study aims to design and describe the feasibility level of mufrodat pocket media in learning Arabic. The research method used is development research, using a Research and Development (R&D) approach. The subjects of the research trial consisted of two material experts and two media experts, as well as 20 class IX students at SMP IT Ummi Ayuni Perbaungan Academic Year 2022/2023. Data analysis techniques for the feasibility of the media using quantitative descriptive analysis. The processing results of this study indicate that the mufrodat pocket media in learning Arabic is considered appropriate by material experts with an average overall score of 78%, and the assessment by media experts as a whole gets an average score of 83% with a very decent category. Furthermore, student assessments in field trials as a whole got an average score of 80% in the very high category. From these results, the developed mufrodat pocket media can be used by teachers and students, especially class IX, SMP IT Ummi Ayuni Perbaungan. It is also recommended for Arabic teachers to utilize mufrodat pocket media as media in learning Arabic at school.